'It's like a safety haven': considerations for the implementation of managed alcohol programs in Scotland. (3rd September 2022) - Parkes, Tessa; Carver, Hannah; Matheson, Catriona; Browne, Tania; Pauly, Bernie
Abstract: Alcohol use disorders (AUDs) are not equitably spread across the population, with some groups, such as people who are experiencing homelessness, being more vulnerable to AUDs due to social inequalities, stigma, and complex social and structural processes. Managed alcohol programs (MAPs) are a harm reduction approach first developed in Canada for those experiencing AUDs and homelessness with positive results. This study aimed to describe the factors that should be considered when implementing MAPs in Scotland. Qualitative data were collected in Scotland via semi‐structured interviews with 29 individuals in a range of roles, including strategic informants ( n  = 12), service staff ( n  = 8), and potential beneficiaries ( n  = 9). Vignettes were used to support data collection. Data were analysed using Framework in NVivo. Participants highlighted six considerations to inform the implementation of MAPs in Scotland: the importance of individualized care; provision of alcohol; holistic care and a focus on well-being; types of settings and service models; staffing; and autonomy and rules. Future research should focus on piloting MAPs in a range of service contexts, using different models of care and settings, to develop an enhanced understanding of their effectiveness in addressing harms and promoting well-being for those experiencing AUDs and homelessness.